1999
DOI: 10.1073/pnas.96.12.6850
|View full text |Cite
|
Sign up to set email alerts
|

Different mutator phenotypes in Mlh1 - versus Pms2 -deficient mice

Abstract: Deficiencies in DNA mismatch repair (MMR) result in increased mutation rates and cancer risk in both humans and mice. Mouse strains homozygous for knockouts of either the Pms2 or Mlh1 MMR gene develop cancer but exhibit very different tumor spectra; only Mlh1 ؊/؊ animals develop intestinal tumors. We carried out a detailed study of the microsatellite mutation spectra in each knockout strain. Five mononucleotide repeat tracts at four different chromosomal locations were studied by using single-molecule PCR or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
76
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(91 citation statements)
references
References 37 publications
13
76
2
Order By: Relevance
“…This study revealed a signi®cant di erence between the expansion and contraction mutations within these repeats, which resulted in elevated frameshift mutant frequencies in Mlh1 7/7 mice (Yao et al, 1999). With the lacI reporter system, however, we did not ®nd a similar di erence in expansions and contractions.…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations
“…This study revealed a signi®cant di erence between the expansion and contraction mutations within these repeats, which resulted in elevated frameshift mutant frequencies in Mlh1 7/7 mice (Yao et al, 1999). With the lacI reporter system, however, we did not ®nd a similar di erence in expansions and contractions.…”
Section: Discussioncontrasting
confidence: 54%
“…The discordant tumor spectrum of the Mlh1 7/7 and Pms2 7/7 mice has suggested a di erential role for these two proteins in tumor formation, likely as a result of di erences in genomic instability. In keeping with this, Yao et al (1999) recently demonstrated that mice de®cient in Mlh1 exhibited a greater degree of instability at repetitive sequences than did mice lacking Pms2.…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…Another set of related experiments studies microsatellite mutations in vivo but in organisms whose mismatch repair system has been knocked out. For an example in mice see [55] and in yeast see [36]. There are many more microsatellite mutations in individuals with deficient mismatch repair systems, and this is informative for studying microsatellite models, but in addition to the rate the pattern of mutations also appears to be different in these individuals.…”
Section: Experiments and Analysismentioning
confidence: 99%